2019
DOI: 10.1039/c9cp00680j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the average molar mass of poly(N-vinylpyrrolidone) on the dimensions and conductivity of silver nanowires

Abstract: Improving the performance of Ag nanowire electrodes by adjusting the reaction conditions and the molar mass of PVP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The PVP layer on AgNWs reported by other works is thicker (>1 nm). 33 Our results may be due to a lower ratio of PVP/AgNO 3 used compared to other classic polyol processes, as well as the amount of PVP being decreased during the purication step. 34 It has previously been shown that the sheet resistance of unannealed AgNW networks is lower when the PVP shell, an electrical insulator, is thinner.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…The PVP layer on AgNWs reported by other works is thicker (>1 nm). 33 Our results may be due to a lower ratio of PVP/AgNO 3 used compared to other classic polyol processes, as well as the amount of PVP being decreased during the purication step. 34 It has previously been shown that the sheet resistance of unannealed AgNW networks is lower when the PVP shell, an electrical insulator, is thinner.…”
mentioning
confidence: 68%
“…Typically in other works the resistance of the AgNW network before post-processing treatments (such as thermal annealing, chemical treatments, laser sintering and mechanical pressing) is much higher. 17,31 The evolution of the resistance versus temperature during a thermal ramp of 5 C min À1 in air was tracked in a sample having an initial sheet resistance of 8 U sq À1 (i.e. before any thermal treatment) (Fig.…”
mentioning
confidence: 99%
“…Typically, high ARs are achieved by dramatically increasing NW length which leads to a decrease in interfacial scattering events. [ 10,13,14 ] However, diameter also often changes in these studies, so it is unclear whether length or diameter is the true driving force behind the observed performance enhancements. Recent studies have shown that charge transport is dominated by the organic phase within the Te–PEDOT:PSS hybrid NW, and the improvement in TE performance is attributed to the interaction of the polymer with the inorganic NW surface.…”
Section: Figurementioning
confidence: 99%
“…Sonntag et al showed the necessity to use a minimum PVP chain length to synthesize AgNWs. They concluded that at their reaction condition the minimum MW of 55 kDa is required to synthesize AgNWs with a small diameter distribution [97]. Coskun et al showed that the PVP : AgNO 3 molar ratios (3 : 1, 4.5 : 1, 6 : 1, 7.5 : 1, 9 : 1, and 11 : 1) affect strongly the final morphology of the silver nanostructures.…”
Section: Effect Of Pvp Concentration and Molecular Weight As Amentioning
confidence: 99%